Education Write Now - Zoul, Jeffrey; Mazza, Joe (Routledge, an imprint of the Taylor & Francis Group, 2018)
"In this innovative new series Education Write Now, ten of education's most inspiring thought-leaders meet for a three-day retreat to think and write collaboratively, and then bring you the top takeaways you need right now to improve your school or classroom. This first volume, edited by Jeff Zoul and Joe Mazza, focuses on the all-important but often uncomfortable concept of change. Each concise chapter addresses how teachers and leaders can do the hard work of enacting change so more students succeed--academically and emotionally. You'll gain practical insights and strategies for changing how we think about ... Embracing Change (Jeff Zoul) Learning (Tony Sinanis) Assessment (Starr Sackstein) Relationships (Kayla Delzer)Mental Health (Joe Mazza) Educational Technology (Thomas Murray) Teacher Engagement (Sanée Bell) Leadership (Amber Teamann) Partnerships (Bob Dillon Communication (Joe Sanfelippo) The royalties generated from this book will support the Will to Live Foundation, a nonprofit foundation working to prevent teen suicide. Dr. Jeffrey Zoul (@jeff_zoul) is a lifelong teacher, learner, and leader. During Jeff's distinguished career in education he has served in a variety of roles, most recently as Assistant Superintendent for Teaching and Learning with Deerfield Public Schools District 109 in Illinois. Jeff also served as a teacher and coach in Georgia before moving into school administration. He has authored many books, including What Connected Educators Do Differently. Dr. Joe Mazza (@joe_mazza) is Lecturer at The University of Pennsylvania's Graduate School of Education. He is the Founder/CEO of MakerDads, a new father and family engagement initiative bringing dads, grand-dads and other male role models together to support student learning through innovation. Joe's innovative work has been featured in 15 books dating back to 2005. Most recently, he co-authored Lead Learners: Creating a Culture of Empathy, Innovation, and Empowerment with Derek McCoy (Routledge, 2018)."--Provided by publisher.